2017
DOI: 10.1103/physreva.95.022323
|View full text |Cite
|
Sign up to set email alerts
|

Universal freezing of asymmetry

Abstract: Asymmetry of quantum states is a useful resource in applications such as quantum metrology, quantum communication, and reference frame alignment. However, asymmetry of a state tends to be degraded in physical scenarios where environment-induced noise is described by covariant operations, e.g., open systems constrained by superselection rules, and such degradations weaken the abilities of the state to implement quantum information processing tasks. In this paper, we investigate under which dynamical conditions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…Recently, Radić et al [28] has proposed an experimental scheme for rotating spin-orbit-coupled BECs by using a suitable control of the BECs. On the other hand, some groups have studied the properties of BECs in various external potentials including harmonic trap [29][30][31], toroidal trap [32,33], concentrically coupled annular traps [34], double-well potential [35][36][37], one-dimensional (1D) optical lattice [38], and so on. It is demonstrated that the shape and dimension of the external potential plays an important role in the stationary states and dynamic properties of the BECs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Radić et al [28] has proposed an experimental scheme for rotating spin-orbit-coupled BECs by using a suitable control of the BECs. On the other hand, some groups have studied the properties of BECs in various external potentials including harmonic trap [29][30][31], toroidal trap [32,33], concentrically coupled annular traps [34], double-well potential [35][36][37], one-dimensional (1D) optical lattice [38], and so on. It is demonstrated that the shape and dimension of the external potential plays an important role in the stationary states and dynamic properties of the BECs.…”
Section: Introductionmentioning
confidence: 99%
“…(Instead, we obtain a very intriguing state. Using such adiabatic processes with negative detunings, Zhang and Dykman [101] theoretically proposed a method for preparation of intriguing quantum states other than cat states. )…”
Section: Kpo Network (Qbm) Opo Network (Cim) Schrödinger Equationmentioning
confidence: 99%
“…Second, collisions of small nuclei with non-uniform distribution of nucleons may offer further stringent tests of the geometry-flow transmutation mechanism, including the event-by-event fluctuations [13,. Moreover, the heavy-light reactions may provide insight into the ground-state clusterization structure in light nuclei, as first proposed in [66,67] and further explored in [68][69][70]. We thus offer a possibility of simulating reactions with 3 He (studied experimentally in [71]) or 3 H nuclei, which may be thought of as small triangles, as well as collisions involving light α-clustered nuclei, such as 7,9 Be (dumbbell), 12 C (triangle), and 16 O (tetrahedron).…”
Section: Introductionmentioning
confidence: 94%